(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
Two types of pneumococcal vaccines for children are registered in Uzbekistan: Prevenar-13 (Pfizer, USA), which contains capsular polysaccharides of thirteen pneumococcal serotypes conjugated with genetically engineered diphtheria toxoid, and 10-valent conjugate vaccine Pnevmosil (India). Until 2020, children were vaccinated with the 13-valent vaccine Prevenar-13, after 2020 - Pnevmosil-10. We conducted a study to assess the humoral immune response (IgG) to 15 pneumococcal CPS in ELISA in children with pneumonia, as well as in relatively healthy children. Analysis of the same sera showed a higher level of IgG in the post-vaccination period to the Prevenar-13 vaccine to a greater extent than to the 10-valent vaccine (1.3-2 times).